Pengaruh Brand Love, Brand Engagement, dan Brand Equity terhadap Repurchase Intention: Studi pada Pengguna Smartphone Samsung di Indonesia - Sita Ningrum Sastri Dewi; Kussudyarsana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Samsung is an electronics brand that is ranked first in 2018 – 2023 as the top brand index category, however, Samsung smartphone products tend to experience a decline from year to year. This shows that the repurchase intention of Samsung smartphone users is not optimal. Therefore, research was used regarding